Методика наукових досліджень студентів вищих навчальних закладів - Петровська, Юліанна; Petrovska, Yuliana (Видавництво Львівської політехніки, 2022)
Висвітлено роль наукових досліджень студентів у вищих навчальних закладах та подальші напрями їх розвитку. Окреслена методика проведення наукових досліджень студентів Інституту архітектури та дизайну спеціальності “Дизайн” упродовж першого (бакалаврського) та другого (магістерського) освітньо-кваліфікаційних рівнів вищої освіти. Проведений аналіз навчальних дисциплін, котрі формують у студентів наукові здібності, методично спрямовують на виконання та презентацію власних наукових розвідок в межах навчального процесу. Розкрито роль наукових досліджень студентів через забезпечення можливості використання науково-технічного потенціалу вищого навчального закладу задля майбутнього розвитку ключових та пріоритетних напрямів науки.

The article highlights the role of student researches at higher educational institutions and further directions of their development, and describes the methodology of scientific researches of students of the Institute of Architecture and Design majoring in Design in the process of their studies for the first (Bachelor’s) and second (Master’s) education and qualification levels. The author conducts the analysis of academic disciplines that form scientific abilities of students, methodically direct them at the implementation and presentation of their own scientific researches within the framework of the educational process. The paper also clarifies the role of student researches through the opportunity to use the scientific and technical potential of a higher educational institution for the sake of future development of key and priority areas of science. The task of the student research work is to acquire knowledge about the types of research, to organize and implement scientific researches, to apply principles and methods of scientific research and research requirements of the Ministry of Education and Science of Ukraine related to the formulation and publication of research results. Educational disciplines of the educational and professional program of Design, which include the research (scientific) component, fully disclose the essence of the scientific research, required skills and methods of conducting researches, as well as the implementation and organization of student independent research work in the process of solving current scientific tasks with the subsequent possibility to publish them in professional scientific journals of the Institute of Architecture and Design, as well as to present them in the form of reports at various conferences. The purpose of organization of scientific researches of students of higher educational institutions is to develop the theoretical knowledge gained in the process of studying. Choosing the direction of the research work, a student thoroughly assesses the relevance of the planned research, formulates the purpose and objectives, determines the object and subject of the research, and forms the methodology of the research work in accordance with the outlined objectives of the study. Motivating students to conduct scientific researches and to publish and test their own researches in the process of studying at higher educational institutions is one of the priorities of the educational system; however the student rating does not always motivate students to achieve this goal. Only a comprehensive approach that includes teaching of special academic disciplines, open system of the academic mobility, scholarships, academic integrity, possibility to participate in student research competitions and grant programs will make students realize the importance of the research work and further prospects of its development.
Methodology of student scientific researches at higher educational institutions
Keywords: наукові дослідження; освітній процес; науково-дослідна практика; освітньо-кваліфікаційний рівень; робоча програма навчальної дисципліни; scientific research; educational process; scientific research training; education and qualification level; work program of the academic discipline; 72.07